Numerical Solution of SEIR epidemic model using differential transformation methods / \c Khairul Hazizi bin Rosmi - Khairul Hazizi Rosmi (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2018)
The main objective of this study is to obtain a numerical solution of SEIR epidemic model which can be achieved through the following sub-objectives ; to develop a new algorithm of DTM for solving SEIR epidemic model ; to derived a Taylor series in 5, 9 and 13-terms ; to approximate the solution of SEIR epidemic model using DTM and RK4 methods ; to compare the solutions of SEIR obtained by DTM and RK4.